Impact of Varicocele on The Expression of Testicular Enzymes Involved in The Transsulfuration Pathway - Azam Shiasi; Marziyeh Tavalaee; Ramesh Monajemi; Dattilo M; Mohammad Hossein Nasr-Esfahani (International Journal of Fertility and Sterility)
Background: Oxidative aggression is a hallmark of varicocele and may depend on decreased reactive ability ofthe endogenous antioxidant system following heat stress. We aimed to investigate the underlying mechanisms.Therefore, the expression of the main enzyme proteins involved in the generation of endogenous antioxidant power,cystathionine beta-synthase (CBS), cystathionine gamma-lyase (CSE), heme oxygenase (HO-1), and also, some ofthe metabolites (methionine, homocysteine, taurine and vitamin B6) reporting on their activity was investigatedusing a surgical varicocele model in rats.Materials and Methods: In this experimental study, thirty male Wistar rats (7-8 weeks old, weighing 180-220 g)were divided into three groups: control, sham, and varicocele. We evaluated sperm parameters and functional tests,as well as the expression of CBS, CSE, and HO-1 proteins using Western blot analysis. Serum levels of methionine,homocysteine, and taurine were analyzed through high-performance liquid chromatography, while vitamin B6concentrations were measured using enzyme-linked immunosorbent assay. For group comparisons, we employedANOVA and the Tukey test, considering a P<0.05 as significant.Results: We observed a significant reduction in both sperm quality and functional parameters. Additionally, therewas a notable decrease in the expression of CBS, CSE, and HO-1 proteins, as well as circulating vitamin B6 levels,in the varicocele group compared to the control and sham groups (P<0.001).Conclusion: The results of this study suggest that one possible cause of increased oxidative stress in varicocelemay be the reduced expression of testicular enzymes involved in the production of endogenous antioxidants, whichare associated with the transsulfuration pathway. However, further studies are needed to confirm these findings.